Relasi Wacana Postkolonial dalam Penggunaan Dua Aksara: Analisis Teori BREAK - Amrina, Yasirly (Jurnal Hata Poda, 2022)
This paper discusses the discourse of postkolonial studies using BREAK theory approach. In this paper discussed two different works or discourses which equally written in the post-colonial period, Tenggelamnya Kapal van der Wijck by Prof. Dr. H. Abdul Malik Karim Amrullah (HAMKA) and “Inilah Sejarah Ringkas Aulia Allah Assalihin Syekh Burhanuddin Ulakan yang Mengembangkan Agama Islam di Daerah Minangkabaui” by Imam Maulana Abdul Manaf Amin al-Khatib (IMAM). The objective of the analysis toward these two works is to see the existence of both works, as two discourses that influence on the ideologi of the society, which can be viewed from various aspects of discourse. Based on the analysis of the discourse by using the BREAK theory, it can be concluded: 1) with a different essence, both works have the same spirit, 2) with the background of the same period and origin of the author, in both works can also be found various ideological and power relations that can connect the two, and 3) from the differences, both works have balance, which will produce the sustainability of both of them.Keywords: postkolonial discourse, ideology and power, theory BREAK